2018
DOI: 10.1111/1365-2435.13222
|View full text |Cite
|
Sign up to set email alerts
|

Hungry for the queen: Honeybee nutritional environment affects worker pheromone response in a life stage‐dependent manner

Abstract: Animal nutritional state can profoundly affect behaviour, including an individual's tendency to cooperate with others. We investigated how nutritional restriction at different life stages affects cooperative behaviour in a highly social species, Apis mellifera honeybees. We found that nutritional restriction affects a worker's queen pheromone response, a behavioural indicator of investment in group vs. individual reproduction. Nutritional restriction at the larval stage led to reduced ovary size and increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
2
18
1
Order By: Relevance
“…For example the variation in the number of susceptible hosts (i.e. the amount of larval brood, for AFB) over a season depends on many intrinsic and external factors [52,53]. Since American foulbrood kills the brood, a shift in the brood-to-worker ratio can be expected, but it is unclear whether larger honeybee colonies are better than smaller colonies at handling such a shift.…”
mentioning
confidence: 99%
“…For example the variation in the number of susceptible hosts (i.e. the amount of larval brood, for AFB) over a season depends on many intrinsic and external factors [52,53]. Since American foulbrood kills the brood, a shift in the brood-to-worker ratio can be expected, but it is unclear whether larger honeybee colonies are better than smaller colonies at handling such a shift.…”
mentioning
confidence: 99%
“…Our results suggest that the blueprint for how nutrients are used in summer and winter bees might be laid down in the larval stage. Others have found changes in adult honey bees due to larval nutrition [ 68 , 69 ], and characterized the responses as anticipatory mechanisms to program adults to better cope with changing environmental conditions (e.g., summer vs. winter colony conditions) [ 69 ]. Additional studies are needed to test this hypothesis, and determine if gene expression in larvae and subsequent behavioral responses as adults reared on seasonal pollens during periods of colony expansion differ from those in larvae reared during colony contraction and preparation for overwintering.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation may be that workers inhabiting hives that contain highly contaminated beeswax or pollen may perceive their environment in a way that makes them more likely to initiate the processes which result in queen events (queen replacement and death). Contrary to many other animals that exhibit increased cooperation under stressful conditions, it has been previously shown that workers that were starved during larval development emerge as adults with a reduced response to queen mandibular pheromone [45]. Queen pheromones are an important signal for modulating cooperative behaviors in workers such as foraging and brood rearing [3], and stressor-mediated changes to pheromone signaling deserve future attention.…”
Section: Discussionmentioning
confidence: 99%